Medical profile and medication consumption of patients presenting for mandibular third molar surgery: Experience in a Saudi Arabian sub-population - Ramat Oyebunmi Braimah; Dawood Ali-Alsuliman; Hakeem Olatunde Agbaje; Yahyah Alsalah; Harit Kanwar Sharma; Nahal Mamdoh Alsawas (Wolters Kluwer Medknow Publications, 2020)
Introduction: Extraction of the impacted third molar is one of the most common minor oral surgical procedures carried out in oral surgery clinic. For the medically compromised, the sequelae and possible complications of third molar surgery can be enormous if such medical conditions are not properly identified and managed adequately. Methodology: Patients presenting for mandibular third molar surgery in the department of oral and maxillofacial surgery, specialty dental center, with medical conditions were recruited into the study from 2015 to 2018. Third molar not indicated for surgical removal were excluded. Data such demographics of patient presenting for third molar extractions, indications for third molar removal, pattern of third molar impaction, medical conditions, and medication consumptions were collected from the electronic medical records. Results: A total of 1024 patients presented for mandibular third molar extraction during the study out of which 123 patients were medically compromised with the prevalence of 12%. There were 32 (26%) male and 91 (74%) female with a M:F = 1:2.8. The age ranged from 17 to 69 years with mean (age ± standard deviation) 31.4 ± 9.6 years. Hypertension/diabetes and hypothyroidism constitute the majority of the compromised condition (35 [28.5%] each) closely followed by hyperthyroidism 23 (18.7%), while hypertension alone constitute the least (1 [0.8%]) case. Conclusion: All patients presenting for the removal of impacted third molar should be investigated for medical conditions by first taking a good and complete medical history to avoid conditions that can put the life of patients under serious risk.